Assisted fertilization with donated oocytes: indications and results - Chuquillanqui Mendoza, Pilar (2023)
Women are increasingly delaying childbearing for different reasons, which causesthem to resort to in vitro fertilization (IVF) treatments with their own oocytes ordonated oocytes to achieve pregnancy. In IVF treatments with donated oocytes,donors are strictly selected and undergo ovarian stimulation with subsequentfollicle aspiration. The recommended age to donate is between 21–34 years old. Amaximum of 6 donations per donor is recommended. The recipient is the personto whom the embryo transfer will be performed and who will carry the pregnancy.Pregnancy rates with this assisted reproduction technique are high and the mostfrequent indications are advanced maternal age and early ovarian failure.